2022
DOI: 10.3389/fmed.2022.875154
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Prediction Model for the Cure of Peritoneal Dialysis-Associated Peritonitis: A Multicenter Observational Study

Abstract: AimPeritoneal dialysis (PD)-associated peritonitis (PDAP) is a severe complication of PD. It is an important issue about whether it can be cured. At present, there is no available prediction model for peritonitis cure. Therefore, this study aimed to develop and validate a prediction model for peritonitis cure in patients with PDAP.MethodsPatients with PD who developed PDAP from four dialysis centers in Northeast China were followed up. According to the region of PD, data were divided into training and validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
9
1
Order By: Relevance
“…One such study reported that higher ALB levels indicated a higher probability of peritonitis recovery 22 ; however, other studies do not support ALB as a predictor 9 , such as ours.…”
Section: Risk Factorscontrasting
confidence: 59%
“…One such study reported that higher ALB levels indicated a higher probability of peritonitis recovery 22 ; however, other studies do not support ALB as a predictor 9 , such as ours.…”
Section: Risk Factorscontrasting
confidence: 59%
“…Another study reported that higher albumin levels indicated a higher probability of peritonitis recovery [ 36 ]. However, our study did not support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes in treating PD-related peritonitis depend on center-level and patient-level characteristics. 56 At the center level, larger center size (higher proportion of dialysis patients treated with PD) and higher center adherence to treatment guidelines are associated with higher peritonitis cure rate. 7 At the individual level, treatment outcomes are closely related to organism type and virulence, treatment timeliness, and peritonitis etiology.…”
Section: Treatmentmentioning
confidence: 99%
“…The recommendation to have early antibiotic therapy is based on three observational studies. [56][57][58] In an Australian study, longer contact-to-treatment time was independently associated with a higher risk of treatment failure, defined as either PD catheter removal or death at 30 days. Each hour of delay in antibiotic treatment was associated with a higher risk of treatment failure by 5.5%.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation